ANALYSIS OF THE CLASSROOM MANAGEMENT OF 3rd OF BACHELOR’S DEGREE CLASS “C” AT THE VICENTE ANDA AGUIRRE HIGH SCHOOL IN THE ACADEMIC PERIOD 2015-2016 - Ramirez Cárdenas, Luis Alexis (2016)
In this important research project it has been analyzed some features deeply connected with the classroom management relate to specific aspects that have to do with it focusing our attention on error correction, classroom organization, and motivation during the teaching-learning process. This research was conducted in the 3rd of Bachelor’s Degree Class “C” at the Vicente Anda Aguirre High School in the academic period 2015-2016 during the month of June of this year. This investigation has the purpose of observing how the teacher manages his English class with the students of the mentioned class in the mentioned institution, however , this particular investigation is focused on how the teacher organizes the class, motivates students, and correct mistakes during the teaching learning process. The ethnographic qualitative method was used to do this research in a clear way, which allows to know classroom management factors and its relationship with the students’ behavior. The level of study of this research is exploratory taking as population the teacher and students of this educational institution that totally are 35 people. Two checklists were designed, the first one about the aspects mentioned above, the second one related to the students’ behavior in order to obtain real and concrete results regarding anomalies that are presented during the development of the class and the problems in the behavior of the students that dull lesson process. As a result of the proposed checklist, it was identified in a concrete way that the teacher handled the class 50% well and 50% wrongly. As a consequence, the students responded with bad behavior to the way that the teacher manages the class.